The imitation game: large language models versus multidisciplinary tumor boards: benchmarking AI against 21 sarcoma centers from the ring trial - Li, Cheng-Peng; Kalisa, Aimé Terence; Roohani, Siyer; Hummedah, Kamal; Menge, Franka; Reißfelder, Christoph; Albertsmeier, Markus; Kasper, Bernd; Jakob, Jens; Yang, Cui (Journal of cancer research and clinical oncology, 2025)
The study aims to compare the treatment recommendations generated by four leading large language models (LLMs) with those from 21 sarcoma centers’ multidisciplinary tumor boards (MTBs) of the sarcoma ring trial in managing complex soft tissue sarcoma (STS) cases.